Jenis Tumbuhan Anggrek Epifit di Kawasan Cagar Alam Jantho Kabupaten Aceh Besar - Hasanuddin Hasanuddin (Universitas Syiah Kuala, 2010)
The study aiming to verify the plant species of epiphytic orchids in the area of Jantho Nature Reservation was conducted in August 2009. The location of the study was divided into three stations, namely: the flow of rivers, hills, and mountains. The research method used in the research was explorative methods. Data were analyzed descriptively. Results showed that 19 species of epiphytic orchids were classified into 12 generas, namely: Aerides, Eria, Phaleonopsis, Dendrobium, Bulbophyllum, Cattleya, Vanda, Pholidata, Arachnis, Coelogyne, Oncidium and Cymbidium. Species dominating the study area were members of the genus Dendrobium, Bulbophyllum, and Coelogyne.